FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KEJADIAN HIPERTENSI PADA MASYARAKAT DI WILAYAH KERJA SIMEULUE TIMUR - Rahmayani Rahmayani (Universitas Pahlawan Tuanku Tambusai, 2022)
Based on data from the East Simeulue Health Center, there were 135 cases of hypertension in the working area of the Health Center. Seeing the high number of hypertension, hypertension needs to get thorough and serious attention. Research objectives To determine the factors associated with the incidence of hypertension in the community in the working area of the Simeulue Timur Health Center. This research is a quantitative research using analytic with cross sectional design. The population of this study were all people who suffer from hypertension at the Simeulue Timur Health Center. Samples were taken by purposive sampling with the object of research being all people with hypertension at the East Simeulue Health Center. Sampling in this study was determined based on the Lemeshow formula. With the desired percent confidence is 95%. So the number of samples is 96 people. This research was conducted in May 2017. Data analysis used Chi-Square analysis. From the research results it is known that there is no relationship between smoking habits and the incidence of hypertension in the community with a p value of 0.078. there is a relationship between socio-economic and the incidence of hypertension in the community with a p value of 0.042. Changing an unhealthy lifestyle to be healthy. For example by not smoking, not drinking alcohol, maintaining dietary consumption patterns so as not to be overweight, and reducing salt consumption to prevent blood pressure from rising.